Chronique journalistique et causerie : rapports, formes, enjeux - Sandrine Carvalhosa (Carnets)
xixth century newspapers have been described as "written conversation". Newspaper columns are the most prominent location of this talk. They were a target of legislative constraints, that were exerted on the press at the time, but they were also a space of freedom. We will endeavour to describe the modalities of this transfer of speech into writing. We will also try to identify the issues at stake. They were considered as inconsistent chatter, and/or as annals in which "future generations [...] will be able to rediscover the intimate character of a bygone era" ; they were missed after the advent of the more factually orientated news reports. It appears to us today as a highly creative literary format.